Measures to Improve Nurses' Pain Management - Rojaye, Justin Oluwasegun (Nursing and Health Sciences Journal (NHSJ), 2024)
Pain is the most common medical issue that older people face in a long-term care facility. Registered nurses have a critical role in helping residents manage their pain. This research looked at measures to improve pain management practices in long-term care facilities in Ontario. The site for this research was a chosen long-term care facility in Ontario, Canada, a 160-bed nursing home for the elderly that provides various nursing and medical care services. Semi-structured focus group interviews lasting about an hour were done. This study's population consisted of 45 nurses. The researcher chose a sample of 25 registered nurses using a purposive sampling strategy. The data was reviewed using qualitative data analysis to detect recurring concerns. This research revealed the necessity of identifying measures to improve pain management and reinforcing good practices in long-term care homes; better pain management practices are necessary to manage pain in a long-term care home. This study demonstrated the importance of recognizing and overcoming measures to improve pain management and reinforce good practices in long-term care homes. Therefore, improved measures to improve pain management practices are required to manage pain in a long-term care home effectively. Education about safe pain management will help to prevent the undertreatment of pain and its negative consequences. The overall benefits of measures to improve pain management practices in long-term care homes expand nurses' clinical knowledge in the care of residents living in nursing homes.